The Holocaust in the borderlands : Interethnic relations and the dynamics of violence in occupied Eastern Europe - Fisher, Gaëlle 1985- HerausgeberIn; Mezger, Caroline 1987- HerausgeberIn; Wallstein-Verlag; International workshop "The Holocaust in the Borderlands: Interethnic Relations and the Dynamics of Violence in Occupied Eastern Europe" (European Holocaust studies, 2019)
Introduction--The Holocaust in the Borderlands : Interethnic Relations and the Dynamics of Violence in Occupied Eastern Europe / Gaëlle Fisher and Caroline Mezger -- The Rise of Antisemitism in the Multiethnic Borderland of Bukovina : Student Movements and Interethnic Clashes at the University of Cernauti (1922-1938) / Anca Filipovici -- Saving Christianity, Killing Jews : German Religious Campaigns and the Holocaust in the Borderlands / Doris L. Bergen -- Hungarians, Germans, and Serbs in Wartime Vojvodina : Patterns of Attitudes and Behaviors towards Jews in a Multiethnic Border Region of Hungary / Linda Margittai -- The Ustasha Youth and the Aryanization of Jewish Property in the Independent State of Croatia, 1941-1945 / Goran Miljan -- Local Agency and the Appropriation of Jewish Property in Romania's Eastern Borderland : Public Employees during the Holocaust in Bessarabia (1941-1944) / Svetlana Suveica -- Listening to the Different Voices : Jewish, Polish, and Ukrainian Narratives on Jewish Property in Nazi-Occupied Eastern Galicia / Anna Wylegala -- "Gornisht oyser verier"?! Khurbn-shprakh as a Mirror of the Dynamics of Violence in German-Occupied Eastern Europe / Miriam Schulz -- Law Decree on Racial Affiliation (April 30,1941) in the Independent State of Croatia / Sanela Schmid -- Fascist Italy and the "Other" : Italianization and the Holocaust in the Triveneto Borderlands, 1918-1948 / Elysa Ivie McConnell -- Vanishing Point Transnistria : Post-Imperial Biographies and German Transnational Continuities in an Age of Empire-Building and Ideologized Mass Violence / Frank Gorlich -- Transcultural Networks in Narratives about the Holocaust in Eastern Europe / Dana Mihailescu -- The Extermination Site Malyj Trostenec : History and Memory / Aliaksandr Dalhuoski -- EHRI Seminars : Researching and Remembering the Holocaust in the Twenty-First Century / Anna Ullrich -- About the Authors.